Golden: Reworking the Psychosocial Maldevelopment of the Obedient Kid - Angeline Noviani (Institute of Research and Community Outreach - Petra Christian University, 2021)
Well-behaved children might seem well, but may actually harbor self-doubt, a strong sense of guilt, and a weak ego identity which will bring them problems emotionally and socially in their later life. This creative work, Golden, was created to raise a discussion on this issue by trying to answer how children may end up developing these traits, what the effects are, and how to recover. To answer this, Erik Erikson’s 8 stages of psychosocial development is used as the base for this coming-of-age drama musical screenplay. It follows the story of an obedient daughter, Annisa. Connected with the theory, Annisa ended with the dystonic “guilt” in the play age stage because of how her mother raised her. Thus, in adolescent stage she lacks emotional resilience in an initiative-based environment. However, since she is enduring the complications and growing a sense of trust, finally, she achieves balance and is healed. Keywords: good child, Erik Erikson, psychosocial maldevelopment, recovery, coming-of-age drama, musical film